2000
DOI: 10.1007/s100870050044
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Response to Differences in Water and Nutritional Status between Zeoponic and Hydroponic Growth Systems

Abstract: containment and liquid and gas phase separation in microgravity by using microporous membranes to control Hydroponic culture has traditionally been used for controlled enviwater delivery to plants. In the present configuration ronment life support systems (CELSS) because the optimal environment for roots supports high growth rates. Recent developments in of this method, nutrient solution flows under a slight zeoponic substrate and microporous tube irrigation (ZPT) also offer negative pressure through microporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Constituent concentrations that have been previously reported to be different between soilgrown and hydroponically grown plants include ash, protein, carbohydrate, Ca, Mg, K, Na, S, and crude fiber (Alamazan et al, 1997;McKeehen et al, 1996;Steinberg et al, 2000;Wheeler et al, 1993Wheeler et al, , 1994. These differences have been attributed to different nutrient content and availability between growth media (Taiz andZeiger, 1998, Resh 1991).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Constituent concentrations that have been previously reported to be different between soilgrown and hydroponically grown plants include ash, protein, carbohydrate, Ca, Mg, K, Na, S, and crude fiber (Alamazan et al, 1997;McKeehen et al, 1996;Steinberg et al, 2000;Wheeler et al, 1993Wheeler et al, , 1994. These differences have been attributed to different nutrient content and availability between growth media (Taiz andZeiger, 1998, Resh 1991).…”
Section: Discussionmentioning
confidence: 92%
“…Such differing conditions have been associated with variability in composition compared to field grown crops (Alamazan et al, 1997;McKeehen et al, 1996;Steinberg et al, 2000;Wheeler, Mackowiak, et al, 1993, 1994. Some of the constituents that have been altered in wheat, soybeans, lettuce, potatoes or sweet potatoes by hydroponic propagation include ash, protein, carbohydrate, Ca, Mg, K, Na, S, and crude fiber (Alamazan et al, 1997;McKeehen et al, 1996;Steinberg et al, 2000;Wheeler et al, 1993Wheeler et al, , 1994Wheeler et al, , 1996. Most of the information available on the nutritional composition of edible plant tissues has been derived from field-grown crops and as such may not be a reliable indication of the nutritional value of crops grown hydroponically.…”
Section: Introductionmentioning
confidence: 98%
“…Fenn et al [14] have shown the addition of 244 Ca, when using urea, has also produced increased radish plant N-use efficiency and 245 production in the field. Previous studies with wheat have also shown that NH4 + 246 released from the exchange sites of the zeolite competed with the uptake of Ca 2+ in 247 wheat plants and resulted in a an NH4-induced Ca deficiency [8,9,10,11,25]. The N 248 levels in zeoponic radishes (6.2-7.1 wt.…”
mentioning
confidence: 98%
“…However, information is still lacking on growing plants under clinorotation due to the difficulties of supplying adequate nutrients and water to the root apparatus up to advanced phenological stages. Hydroponic systems that release the nutrient solution through microporous materials (Wright et al, 1988;Koontz et al, 1990;Steinberg et al, 2000) could be the most suitable systems for growing plants under simulated microgravity conditions.…”
Section: Introductionmentioning
confidence: 98%